YTH domain family 2 orchestrates epithelial-mesenchymal transition/proliferation dichotomy in pancreatic cancer cells. Issue 23 (2nd December 2017) - Chen, Jixiang; Sun, Yaocheng; Xu, Xiao; Wang, Dawei; He, Junbo; Zhou, Hailang; Lu, Ying; Zeng, Jian; Du, Fengyi; Gong, Aihua; Xu, Min
ABSTRACT: Recent studies show that YTH domain family 2 (YTHDF2) preferentially binds to m 6 A-containing mRNA regulates localization and stability of the bound mRNA. However, the role of YTHDF2 in pancreatic cancers remains to be elucidated. Here, we find that YTHDF2 expression is up-regulated in pancreatic cancer tissues compared with normal tissues at both mRNA and protein levels, and is higher in clinical patients with later stages of pancreatic cancer, indicating that YTHDF2 possesses potential clinical significance for diagnosis and prognosis of pancreatic cancers. Furthermore, we find that YTHDF2 orchestrates two cellular processes: promotes proliferation and inhibits migration and invasion in pancreatic cancer cells, a phenomenon called "migration-proliferation dichotomy", as well as epithelial-mesenchymal transition (EMT) in pancreatic cancer cells. Furthermore, YTHDF2 knockdown significantly increases the total YAP expression, but inhibits TGF-β/Smad signaling, indicating that YTHDF2 regulates EMT probably via YAP signaling. In summary, all these findings suggest that YTHDF2 may be a new predictive biomarker of development of pancreatic cancer, but a serious consideration is needed to treat YTHDF2 as a target for pancreatic cancer.